Is depreciation fraud detectable using ADTFA and DAAT financial models? A case study - Kumar, Sunil (International Journal of Financial, Accounting, and Management, 2024)
Purpose: Financial statement fraud, which is usually committed by insiders, aims to present a company positively and benefit fraudsters. Insiders commit fraud to deceive investors or hide their mistakes. This occurs in companies with weak control and unethical leaders. Prevention is important; however, early detection is crucial. Depreciation fraud manipulates the depreciation schedule to make financial statements look better. This involves inflating asset values and reducing expenses. Detecting depreciation fraud is difficult, and has severe consequences. Such activities can lead to penalties for both individuals and companies. Companies require accurate records, and auditors must review statements thoroughly to prevent and uncover fraud. New models were used to identify depreciation fraud in defaulting companies. Research methodology: Forensic accountants may analyze depreciation fraud. We use Depreciation Accumulated after Tax (DAAT) to accurately find depreciation fraud by the company. A comparatively low or negative impact indicates depreciation fraud. The ADTFA and DAAT financial models can be used to trace depreciation fraud. Results: The results are remarkable and should be tested in further depreciated fraud companies to detect their financial health position early. Limitations: Detecting depreciation fraud is difficult because of various factors, including complex accounting methods, subjective estimates, and lack of external verification. Contribution: This helps to account for users and investors, researchers detect depreciation fraud earliest, and present its financial accounting report. Novelty: The researcher may adopt and push validated reliability through ADTFA and DAAT tests to detect depreciation fraud.